Pembentukan Karakter Religius Siswa Sekolah Dasar Melalui Implementasi Budaya Sekolah - Salsabila, Salsabila; Priatmoko, Sigit (ZAHRA: Research and Tought Elementary School of Islam Journal, 2023)
This research is motivated by the rise of cases regarding the decline in moral values, which makes the world of education considered to have failed to educate the younger generation. This is because many educational institutions prioritize cognitive values and override moral values. Therefore the government immediately responded to this, and emphasized the application of student character cultural values in the hope of creating a nation of quality and character. In accordance with the aspect of national education goals in Law No. 20 of 2003. The purpose of this study was to describe the implementation of 9S school culture in the formation of the religious character of students at SD Plus Al-Kautsar Malang City. This study uses a descriptive qualitative approach. The process of collecting data using interview techniques, observation, and documentation. Data analysis methods consist of data reduction, data presentation, and drawing conclusions. The validity of the data is done by triangulation and member checks. The results of the study show that the 9S school culture contributes well to the formation of students' religious character values, besides that it can form other values that have been described by PPK (Strengthening Character Education). Factors supporting the implementation of the 9S school culture include the enthusiasm of teachers, students, school employees, parents, facilities and infrastructure in the form of posters supporting the 9S school culture, and a conducive school environment. While the inhibiting factors include teacher consistency in implementing and overseeing the 9S school culture, parenting patterns, and the social environment of student peers.